The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Evaluating Health Promotion 2004
DOI: 10.1093/acprof:oso/9780198528807.003.0007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating social marketing interventions

Abstract: Social marketing is a process for designing and modifying health promotion interventions. This chapter focuses on the evaluation of social marketing. Topics discussed include the PERForM performance framework for social marketing, measures of social marketing performance, and the social marketing evidence base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…24 The Z-scores for the anthropometric measurements were calculated by discarding the lower and upper 1% of the distribution. 25 Chapman (2010). prevalence of parasites or bacteria in stool and drinking water samples (respectively), which is consistent with the fact that there were no effects on the incidence of diarrhea, micronutrient malnutrition, or anemia.…”
Section: Resultssupporting
confidence: 78%
“…24 The Z-scores for the anthropometric measurements were calculated by discarding the lower and upper 1% of the distribution. 25 Chapman (2010). prevalence of parasites or bacteria in stool and drinking water samples (respectively), which is consistent with the fact that there were no effects on the incidence of diarrhea, micronutrient malnutrition, or anemia.…”
Section: Resultssupporting
confidence: 78%
“…A national research study found that 76.6% of retail outlets surveyed had never sold a condom in 2002 [36]. Population Services International began a national condom promotion program in early 2002 [37] using a three-pronged approach: (1) a national media campaign promoting condoms (Figure 1); (2) increased widespread condom availability within the private sector to destigmatize condom use; and (3) targeted condom promotion to high-risk groups such as sex workers [38]. The impact of such efforts on condom sales has been dramatic.…”
Section: The Local and International Response To The Epidemicmentioning
confidence: 99%
“…These three summary constructs proximally explain a person’s use of preventive or curative health products and services and/or risk-reducing behavior 19–24. In other words, opportunity, ability, and motivation facilitate or inhibit the behavior, and they can be enhanced, increased, or positively changed within the target audience by the intervention agency 25,26. The MOA framework has been applied in several behavior-change contexts.…”
Section: Introductionmentioning
confidence: 99%